The Impact of Artificial Intelligence and Robotic Process Automation on Accounting Performance and Employee Satisfaction in Financial Services in Indonesia - Judijanto, Loso; Zaman, Delfian; Louisther, Hansen; Ghurabillah, Ghurabillah; Hasibuan, Renika (The Es Accounting And Finance, 2025)
This study examines the impact of Artificial Intelligence (AI) and Robotic Process Automation (RPA) on accounting performance and employee satisfaction in the financial services sector in Indonesia. Using a quantitative approach, data were collected from 150 respondents and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that AI significantly enhances accounting performance through faster reconciliation, consistent data processing, and cost reduction. Similarly, RPA contributes positively to accounting performance by automating repetitive tasks and improving process scalability. AI and RPA also positively affect employee satisfaction, with RPA having a stronger influence. This is attributed to the reduction in job-related stress and improved work-life balance facilitated by automation. The study highlights the complementary roles of AI and RPA in enhancing organizational outcomes and employee well-being. Practical implications suggest the need for employee training, transparent communication, and balanced technology strategies to maximize the benefits of automation in the financial services industry.